Effect of vitamin D supplementation on thyroid hormones in hypothyroid females of child-bearing age: a systematic review - Irshad, Ghazala; Kaukab, Nabeela; Hidayat, Mariyah (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the impact of vitamin D supplementation on thyroid function and autoimmunity in hypothyroid females of child-bearing age. Method: The systematic review was conducted from October 2024 to May 2025, and comprised search on PubMed, Cochrane Library, Google Scholar and the International Clinical Trials Registry Platform databases using predefined key words and medical subject heading terms, with no date restrictions, up to May 2025. The studies included were randomised controlled and clinical trials in hypothyroid females receiving vitamin D supplementation, and reporting thyroid-stimulating hormone and anti-thyroid peroxidase antibody values. Three reviewers independently screened records, extracted data, and assessed bias using the Cochrane Risk of Bias tool. Results: Of the 384 identified records, 11(2.86%) were analysed in detail. Dosages of vitamin D administered ranged from 800 IU/day to 60,000 IU/week, over 2-24 weeks. Of the total, 9(81.81%) studies reported significant thyroid-stimulating hormone reduction, particularly with >50,000 IU/week dose and baseline deficiency correction, whereas anti-thyroid peroxidase antibodies declined in eight autoimmune hypothyroidism studies with three documented more than 50% reduction from baseline. Conclusion: Vitamin D supplementation, especially at higher doses and longer durations, could lower thyroid-stimulating hormone and thyroid autoantibodies in hypothyroid females of reproductive age. PROSPERO Registration No.: CRD42023469980. Key Words: Vitamin D, Hypothyroidism, Thyroid hormones, Anti-TPO antibodies, Reproductive age, Randomised controlled trials, Clinical trials.